Jom Solat-iVAK: an interactive android mobile application in learning wudhu and salah for children with learning disabilities / Nur Anati Nabilah Mat Husin and Nurulhuda Zainuddin - Mat Husin, Nur Anati Nabilah; Zainuddin, Nurulhuda (Faculty of Computer and Mathematical Sciences, 2022)
Jom Solat-iVAK Mobile Application is an interactive android mobile application in learning Wudu and Salah for children with learning disabilities. The existing and new criteria for evaluating Wudu and Salah mobile applications implemented in this project have been improved and developed from the level of quality assessment to a deeper element of Wudu and Salah mobile application design and interface. Similarly, additional aspects such as language, examples used, and compliance with the Islamic Foundation of Shari'ah, which relies on primary and secondary sources of knowledge such as the Qur'an, Sunnah, and Fiqh Science, have been considered to determine whether it is appropriate for children with learning disabilities. According to the research, developers should design and develop additional Wudu and Salah mobile applications for children with learning disabilities, particularly those with a unique education that relates to their learning style and entertainment aspects. This study also identifies some prerequisites and criteria for developing Wudu and Salah applications for Muslim children, particularly those with learning disabilities. This application is divided into three sections, each represented by a different module: Wudu, Salah, and Quiz. Quizzes allow children to evaluate their progress during a learning session. This application followed Visual, Auditory, and Kinesthetics (VAK) learning styles components that are truly suitable for children with learning disabilities. They can learn by reading (Visual), hearing audio (Auditory), and watching videos (Kinesthetics). As a result, children will value and enjoy their studies, and they will be able to quickly absorb knowledge and correctly say prayer.